Airway epithelial repair in health and disease: Orchestrator or simply a player?. Issue 3 (25th January 2016) - Iosifidis, Thomas; Garratt, Luke W.; Coombe, Deirdre R.; Knight, Darryl A.; Stick, Stephen M.; Kicic, Anthony
Abstract: Epithelial cells represent the most important surface of contact in the body and form the first line of defence of the body to external environment. Consequently, epithelia have numerous roles in order to maintain a homeostatic defence barrier. Although the epithelium has been extensively studied over several decades, it remains the focus of new research, indicating a lack of understanding that continues to exist around these cells in specific disease settings. Importantly, evidence is emerging that airway epithelial cells in particular have varied complex functions rather than simple passive roles. One area of current interest is its role following injury. In particular, the epithelial‐specific cellular mechanisms regulating their migration during wound repair remain poorly understood and remain an area that requires much needed investigation. A better understanding of the physiological, cellular and molecular wound repair mechanisms could assist in elucidating pathological processes that contribute to airway epithelial pathology. This review attempts to highlight migration‐specific and cell‐extracellular matrix (ECM) aspects of repair used by epithelial cells under normal and disease settings, in the context of human airways.